2019
DOI: 10.1007/s00167-019-05790-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolated gracilis tendon harvesting is not associated with loss of strength and maintains good functional outcome

Abstract: Purpose The gracilis tendon is a commonly used autologous graft. Most information on knee function and outcomes after its harvest is related to both semitendinosus‐ and gracilis tendon harvest. Therefore this study analyzed the effect of isolated gracilis tendon harvest from healthy, uninjured knees on thigh muscle strength and patient reported outcome measures (PROMs). Methods Stabilization of the acromioclavicular joint because of chronic instability was performed with autologous gracilis tendon in 12 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…The hamstring tendons are the most used grafts; however, palmaris longus [17], flexor carpi radialis, peroneus longus [18] and tibialis anterior tendons [19] have been used as well. Gracilis tendon autograft was chosen because it has been demonstrated that isolated gracilis tendon harvesting is not associated with loss of strength in knee flexion, internal tibial rotation and thigh adduction [20]. In addition, preserving the native semitendinosus may be beneficial especially in young patients to keep a strong graft for any possible further surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…The hamstring tendons are the most used grafts; however, palmaris longus [17], flexor carpi radialis, peroneus longus [18] and tibialis anterior tendons [19] have been used as well. Gracilis tendon autograft was chosen because it has been demonstrated that isolated gracilis tendon harvesting is not associated with loss of strength in knee flexion, internal tibial rotation and thigh adduction [20]. In addition, preserving the native semitendinosus may be beneficial especially in young patients to keep a strong graft for any possible further surgeries.…”
Section: Discussionmentioning
confidence: 99%